Evidence‐based practice integration in hospital wards-The complexities and challenges in achieving evidence‐based practice in clinical nursing - Åste Renolen; Esther Hjälmhult; Sevald Høye; Lars Johan Danbolt; Marit Kirkevold (Wiley, 2019)
Abstract Aim Exploring the processes involved in two different strategies to integrate evidence‐based practice into nursing practice. Design Classical grounded theory methodology was used. Methods Data were collected through 90 hr of observation and 4 focus groups among clinical nurses in two different hospital wards. Results We identified a multidimensional evidence‐based practice integration framework that illuminates the complexities involved in the integration process. The dimensions were approaches to evidence‐based practice, positions of evidence‐based practice and levels of evidence‐based practice. The interactions between the dimensions gave five combinations; an explicit evidence‐based practice performed as a parallel to daily work at the systems level, an implicit evidence‐based practice integrated into daily work at the systems level, an explicit evidence‐based practice integrated into daily work at the individual level, an explicit evidence‐based practice integrated into daily work at the systems level and an implicit evidence‐based practice integrated into daily work at the individual level.